A Multicomponent Gel for Nitric Oxide Photorelease with Fluorescence Reporting. Issue 3 (28th January 2015) - Fraix, Aurore; Kandoth, Noufal; Gref, Ruxandra; Sortino, Salvatore
Abstract An engineered hydrogel platform has been developed, in the absence of any toxic solvents or reagents, by the supramolecular self‐assembly of three different components: a poly‐β‐cyclodextrin polymer, a hydrophobically modified dextran, and a photoactivatable bichromophoric molecular conjugate designed to photorelease nitric oxide (NO) with a fluorescent reporting function. The multivalent character of the interactions between the all components and the poor solubility of the conjugate in aqueous medium ensure the stability of the hydrogel and the lack of leaching of the photoactive cargo from the gel network under physiological conditions, even in the absence of protective coating agents. The photochemical properties of the molecular conjugate are retained in the supramolecular matrix, as demonstrated by the remote‐controlled release of NO upon visible light excitation simultaneously to the activation of a fluorescent reporting function, which allows easy monitoring of the photoreleased NO.